Huperzine A for Alzheimer's disease: a systematic review and meta-analysis of randomized clinical trials. - Guoyan Yang; Yuyi Wang; Jinzhou Tian; Jian-Ping Liu (PLoS ONE, 2013)
Background Huperzine A is a Chinese herb extract used for Alzheimer's disease. We conducted this review to evaluate the beneficial and harmful effect of Huperzine A for treatment of Alzheimer's disease. Methods We searched for randomized clinical trials (RCTs) of Huperzine A for Alzheimer's disease in PubMed, Cochrane Library, and four major Chinese electronic databases from their inception to June 2013. We performed meta-analyses using RevMan 5.1 software. (Protocol ID: CRD42012003249). Results 20 RCTs including 1823 participants were included. The methodological quality of most included trials had a high risk of bias. Compared with placebo, Huperzine A showed a significant beneficial effect on the improvement of cognitive function as measured by Mini-Mental State Examination (MMSE) at 8 weeks, 12 weeks and 16 weeks, and by Hastgawa Dementia Scale (HDS) and Wechsler Memory Scale (WMS) at 8 weeks and 12 weeks. Activities of daily living favored Huperzine A as measured by Activities of Daily Living Scale (ADL) at 6 weeks, 12 weeks and 16 weeks. One trial found Huperzine A improved global clinical assessment as measured by Clinical Dementia Rating Scale (CDR). One trial demonstrated no significant change in cognitive function as measured by Alzheimer's disease Assessment Scale-Cognitive Subscale (ADAS-Cog) and activity of daily living as measured by Alzheimer's disease Cooperative Study Activities of Daily Living Inventory (ADCS-ADL) in Huperzine A group. Trials comparing Huperzine A with no treatment, psychotherapy and conventional medicine demonstrated similar findings. No trial evaluated quality of life. No trial reported severe adverse events of Huperzine A. Conclusions Huperzine A appears to have beneficial effects on improvement of cognitive function, daily living activity, and global clinical assessment in participants with Alzheimer's disease. However, the findings should be interpreted with caution due to the poor methodological quality of the included trials.